PENYUTRADARAAN DENGAN GAYA OBSERVASIONAL PADA DOKUMENTER BIOGRAFI “TEGUH ING PANGURIPAN” DI SLEMAN - Nindia Aprilia; Oktafiani Herlina; Antonius Janu Haryono (AKADEMI KOMUNIKASI RADYA BINATAMA, 2023)
ABSTRACT The documentary work entitled Teguh Ing Panguripan is a documentary program that tells the profile of Teguh Rahardjo. Here he is deaf and speech impaired, but in his life he can still live normally both at work and interacting with other people. The life he lives certainly has various obstacles and problems, but his family and the people around him are able to help him in his life. The title of this work has a meaning that reflects the character, namely